Stenting of high-tortuous ducts in duct-dependent pulmonary circulation: essential points to consider before deciding on stenting - Nathalie Mini (Frontiers in Cardiovascular Medicine, 2023)
Despite the advancements in the technique of duct stenting (DS) in patients with duct-dependent pulmonary circulation (DDPC) and the valuable role of DS in preventing the risk of surgical creation of shunts and early repair, not all ducts are amenable to being stented, and not all interventions with DS are safe and can achieve positive outcomes. Very few studies focusing on tortuous ducts have been conducted until now. Their results showed that stenting of highly tortuous ducts has the same risk as surgical options. This type of stenting has greater possibility of complications, early in-stent thrombosis, and stent failure than do other duct types. In such cases, the surgical options could be superior to DS and have better outcomes. This report aims to review the very scarce available data about stenting of high-tortuous ducts and criticisms of performing DS in ducts associated with pulmonary stenosis and to highlight the essential points that must be considered before deciding on intervention.